Glutamate, GABA and dopamine hydrochloride concentration effects on the conductivity and impedance of cerebrospinal fluid - Xing, Paul; Miled, Mohamed Amine; Sawan, Mohamad (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
This paper shows the effect of neurotransmitter concentrations on the local conductivity and impedance of the cerebrospinal fluid in addition to their biological effects. Three neurotransmitters are studied: glutamate and gamma-Aminobutyric acid (GABA), which are the major excitatory and inhibitory neurotransmitters respectively, and dopamine, which is involved in many psychiatric disorders such as Parkinson's disease, drug's addiction and schizophrenia. We used different concentrations of artificial cerebrospinal fluid (ACSF) since its conductivity is too high. Obtained results prove that neurotransmitter concentration can be detected by sensing the conductivity and the impedance of the ACSF. Indeed, when the glutamate concentration increases from 6 mM to 58 mM the conductivity of 0.5% ACSF jumps from 0.03 S/m to 0.07 S/m while its impedance decreases from 2.8 kΩ to 1.5 kΩ. However, GABA concentration does not affect the conductivity of the ACSF but we observed a significant decrease of impedance of the 0.5% ACSF solution from 6.5 kΩ to 4 kΩ when GABA concentration increases from 5 mM to 500 mM. In the case of dopamine hydrochloride, an important change of conductivity and impedance is observed with 10% ACSF solution which varies from 0.3 S/m to 1.2 S/m and from 460 Ω to 200 kΩ respectively when the dopamine concentration drops from 5 mM to 100 mM.